An enigmatic carnivorous plant: ancient divergence of Drosophyllaceae but recent differentiation of Drosophyllum lusitanicum across the Strait of Gibraltar. Issue 6 (17th August 2020) - Martín-Rodríguez, Irene; Vargas, Pablo; Ojeda, Fernando; Fernández-Mazuecos, Mario
Abstract : Drosophyllaceae is the only plant family endemic to the Mediterranean Floristic Region. It includes a single species, the carnivorous Drosophyllum lusitanicum, which is hypothesised to be a relict plant. Our aim here is to reconstruct the evolutionary history of Drosophyllum to evaluate whether the African-European disjunction across the Strait of Gibraltar is the result of vicariance or long-distance dispersal, and to assess the role of the Strait of Gibraltar area in the long-term persistence of this species. A time-calibrated phylogeny based on nuclear ITS sequences estimated a mid-Eocene to mid-Miocene age (19–44 Mya) for the common ancestor of Drosophyllaceae and its sister clade (Ancistrocladaceae-Dioncophyllaceae). In contrast, differentiation of ITS lineages of Drosophyllum occurred in the Pleistocene, after the opening of the Strait of Gibraltar (ca. 5 Mya). A haplotype network built using two plastid DNA regions revealed six haplotypes in Drosophyllum, five of which occur in the Strait of Gibraltar area. Four of the six haplotypes were present in both European and African populations. Therefore, although Drosophyllaceae diverged from the closest relatives in ancient times, the current distribution of Drosophyllum is relatively recent (Pleistocene). Given that the Strait of Gibraltar was already open in the Pliocene, the disjunct distribution of this species between Europe and Africa appears to be the result of multiple events of long-distance dispersal. Species distribution modelling (SDM) was used to reconstruct the potential distribution of Drosophyllum throughout the late Quaternary (last interglacial, Last Glacial Maximum, mid-Holocene and present), which revealed long-term persistence around the Strait of Gibraltar and in the south-western Iberian Peninsula. The Strait of Gibraltar area and the south-western Iberian Peninsula may have shared similar climatic conditions, and thus acted as refugia for Drosophyllum throughout the late Quaternary.